Técnicas de creación y manipulación de imágenes de estructuras orgánicas tridimensionales. Nuevos entornos de aplicación didáctica - Juanes, J. A.; Zoreda, J. L.; Vacas Peña, José Manuel; Riesco, J. M.; Vázquez, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
The development of computer -generated images opens new perspectives in the field of teaching. These techniques permit geometric modelling of three-dimensional structures, allowing the production and manipulation of real images and the numerical and graphic characterization of two -three-dimensional contours. The procedure proposed is based on the manipulation, by geometric (turns, traslations) and algebraic (addition, intersection) operations, of an initially finite set of surfaces (elipsoids, paraboloids, cylinders and planes), defined by their parameters, for teaching purposes.